Knowledge and training of social workers in the health field of the province of Granada in the face of euthanasia - Jiménez-Rodríguez, José Manuel (Acciones e Investigaciones Sociales, 2022)
Introduction: Euthanasia is a legislative measure recently implemented in the health systems of the Spanish territory. Guarantor of a calm end of life, it avoids the physical and emotional suffering of the patient when the disease is irreversible. Its implementation requires sufficient knowledge and a favorable aptitude to facilitate its development. Health social workers are an appropriate profile to start the discourse on dignified death and report on the formal and informal aspects surrounding euthanasia. The objective of this research is to identify the knowledge and predisposition of primary care health social workers about euthanasia. Material and methods: Cross-sectional descriptive observational study aimed at all primary care social health workers in the province of Granada whose sample universe represents N=40. For data collection, the self-administered questionnaire was used. A descriptive and bivariate analysis was performed using Epi Info. Results: 39 individuals participated in the study. The knowledge that these participants have about the euthanasia law supposes an average of 3.84 (Sd. 1.98). Only 28.2% have read the documents that regulate the provision of aid to die in Andalusia. The ability to accompany in the management of grief represents an average of 7.02 (Sd. 2.45). Discussion: The knowledge of health social workers about euthanasia is scant. Few have read the regulatory documentation for euthanasia. This ignorance does not limit the perception they have about this benefit, presenting a favorable attitude towards it.
Keywords: euthanasia; social work; Health; knowledge; attitude.